Local skin flap procedure for repair of rectovaginal fistula: A case report. (October 2022) - Yamada, Kazunosuke; Hirose, Taro; Ojima, Hitoshi
Abstract: Introduction: Rectovaginal fistula (RVF) is an increasingly common rectal surgery complication. Although various RVF closure operations have been reported, no one approach is considered ideal. Consequently, some patients must undergo more complex and technically challenging surgical procedures. We describe the successful use of simple local skin flap plasty for RVF repair. Presentation of case: A 74-year-old Japanese female developed RVF after robot-assisted laparoscopic proctectomy with intersphincteric resection, hand-sewn coloanal anastomosis, and a temporary ileostomy. Three months later, reconstructive surgery was performed using a local flap. The fistula was successfully closed and healed well without complications. Discussion: A local flap consists of the skin and subcutaneous tissue harvested from a nearby site that maintains its intrinsic blood supply. Conclusion: This novel approach to RVF repair appears simple, effective, and safe. Highlights: A local flap consists of the skin and subcutaneous tissue harvested from a nearby site. A local flap is simple, less invasive, and considered early in the process. A local flap can be one of the RVF treatments.